Hubungan Rasio Lingkar Pinggang Panggul Dengan Kadar Low Density Lipoprotein Pasien Penyakit Jantung Di Poliklinik Jantung RSUD Brigjend. H. Hasan Basry Kandangan - Yuliana Salman; Erhan Effendi; Rianti Esmeralda (HB PRESS, 2016)
The waist-to-hip circumference ratio is an anthropometric method to describe the distribution of fat in the body, especially in the areas of subcutaneous and abdominal fatty tissue. Fat cells located in the abdominal wall has a larger size that is dominated by low-density lipoprotein which is often a major factor in cardiovascular disease. To determine the correlation between waist to hip circumference ratio with low density lipoprotein levels in heart disease patients with heart polyclinic Brigjend H. Hasan Basry Kandangan Hospital. This study was an observational analytic study with the hypotheses associative method using cross sectional design. The number of respondents as many as 78 research samples using accidental sampling technique that met study inclusion and exclusion criteria. The data were analyzed using Spearman's correlation test. The results showed that of 78 respondents there were 14 respondents who have pelvic ideal ratio of waist circumference and 64 who have a waist circumference ratio is not ideal. Of the 78 respondents which had normal levels of low density lipoprotein amounted to 32 respondents, is rather high as 21 respondents, and as of 25 respondents. This research shows there is a significant correlation with the weak force between waist to hip ratio with levels of low density lipoprotein respondents, r = 0,320, p = 0,004. Keywords : Waist Hip Ratio, Low Density Lipoprotein, Heart Disease